2019
DOI: 10.1111/avj.12780
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoma in Australian Border Collies: survey results and pedigree analyses

Abstract: Objectives The aims of this study were to (1) describe the results of a survey on the clinical features of lymphoma in Australian Border Collies and (2) investigate familial clustering of lymphoma‐affected dogs by means of pedigree analyses. Methods Clinical and pedigree information was collected from surveys completed by owners or breeders of Australian Border Collies. Relationships between dogs were derived from pedigree data and kinship was analysed by network and cluster‐based algorithms. Results A total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…Previous studies have focused on age at cancer diagnosis, or age at death from cancer, for individual breeds [16][17][18] or for specific cancer types [19][20][21], making the findings difficult to generalize to other breeds or to mixed-breed dogs. Some of the larger, population-based studies that incorporated a more diverse selection of breeds were conducted in Europe [2,3,22,23] where common breeds may not be representative of breeds that are common in the United States; additionally, cancer incidence and cancer types observed in these studies may be different from those seen in a US population, given environmental differences and spay/neuter rates in Europe versus the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have focused on age at cancer diagnosis, or age at death from cancer, for individual breeds [16][17][18] or for specific cancer types [19][20][21], making the findings difficult to generalize to other breeds or to mixed-breed dogs. Some of the larger, population-based studies that incorporated a more diverse selection of breeds were conducted in Europe [2,3,22,23] where common breeds may not be representative of breeds that are common in the United States; additionally, cancer incidence and cancer types observed in these studies may be different from those seen in a US population, given environmental differences and spay/neuter rates in Europe versus the United States.…”
Section: Introductionmentioning
confidence: 99%
“…A study from the University of Sydney addresses the potential genetic background for lymphoma in Australian Border Collies concludes that there is a heritable component to this disease and that further tests are needed to look at the genetic risk including the risk of disease in young dogs …”
Section: Small Animalsmentioning
confidence: 99%
“…A study from the University of Sydney addresses the potential genetic background for lymphoma in Australian Border Collies concludes that there is a heritable component to this disease and that further tests are needed to look at the genetic risk including the risk of disease in young dogs. 3 The aetiology of lymphoma is unclear, but overseas studies have identified a role for genetic mutations. In a study promoted via the Border Collie Club of NSW, owners and breeders were asked about their dogs' current health status and those whose dogs had a history of lymphoma were asked additional questions.…”
Section: Small Animalsmentioning
confidence: 99%
“…Border Collies are a popular breed worldwide and are at increased risk of lymphoma compared to the general population [ 36 ]. Lymphomas in Border Collies are most often of the B-cell immunophenotype (84 to 91% of cases) [ 5 , 37 ]. We previously reported the results of a survey of lymphoma of Border Collies in Australia and identified 28 cases with a common female ancestor [ 37 ], suggesting a potential heritable risk.…”
Section: Introductionmentioning
confidence: 99%